Polyolefin composition obtained from recycled polyolefin

The challenges in sustainability and performance of existing polyolefin compositions are solved by developing a polymer composition comprising propylene homopolymer, propylene ethylene copolymer and recycled polyethylene, and the mechanical properties and sustainability improvement of the material are achieved.

CN119546698AActive Publication Date: 2025-02-28BASELL POLIOLEFINE ITALIA SRL
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380053914.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-04
Filing Date
2023-07-26
Publication Date
2025-02-28
Estimated Expiration
2043-07-26

AI Technical Summary

Technical Problem

Existing polyolefin compositions have problems with sustainability, especially their production relies on non-renewable resources, while recycled polymers have challenges in quantitative separation and performance, resulting in limitations in practical applications.

Method used

A propylene polymer composition is developed, which comprises 50-80% propylene homopolymer or propylene ethylene copolymer, 20-50% blend, which comprises propylene ethylene copolymer and recycled polyethylene. The composition optimizes the mechanical properties and sustainability of the material by adjusting the melt flow rate and ethylene content.

Benefits of technology

The composition exhibits improved characteristic curves in terms of impact and modulus values, improving the mechanical properties of the material, while reducing dependence on non-renewable resources and improving the sustainability of the material through the use of recycled polymers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005242754110000071
    Figure BDA0005242754110000071
  • Figure BDA0005242754110000072
    Figure BDA0005242754110000072
  • Figure BDA0005242754110000081
    Figure BDA0005242754110000081
Patent Text Reader

Abstract

A propylene polymer composition comprising: A) from 50% to 80% by weight of a propylene homopolymer or a propylene ethylene copolymer; b) from 50% to 20% by weight of a blend comprising: T1) from 10% to 50% by weight of a propylene ethylene copolymer comprising from 8.0% to 20.0% by weight of ethylene derived units; t2) from 20% to 80% by weight of recycled polyethylene (r-PE).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to soft polypropylene compositions comprising recycled elastomeric materials that can be used to prepare extruded articles. Background Art

[0002] Due to the valuable properties typical of polyolefins, such as chemical inertness, mechanical properties and non-toxicity, polyolefin compositions having elastic properties while maintaining good thermoplastic behavior have been used in many application areas. In addition, they can be advantageously converted into finished products using the same techniques used for thermoplastic polymers. In particular, flexible polymer materials are widely used in the medical field, as well as for packaging, extrusion coating, and wire and cable covering.

[0003] Elastic polypropylene compositions that retain good thermoplastic behavior have been obtained in the art by sequential copolymerization of propylene, optionally containing a small amount of olefin comonomer, and subsequently ethylene / propylene or ethylene / α-olefin copolymer mixtures. Catalysts based on halogenated titanium compounds supported on magnesium chloride are generally used for this purpose. For example, EP-A-472946 describes a flexible elasto-plastic polyolefin composition comprising, by weight: A) 10 to 50 parts of isotactic propylene homopolymer or copolymer; B) 5 to 20 parts of an ethylene copolymer that is insoluble in xylene at room temperature; and C) 40 to 80 parts of an ethylene / propylene copolymer that contains less than 40% by weight of ethylene and is soluble in xylene at room temperature; the intrinsic viscosity of the copolymer is preferably from 1.7 dl / g to 3 dl / g. The composition is relatively flexible and has good elastic properties.

[0004] Additionally, polyolefin compositions, although appreciated in terms of performance, raise concerns in terms of sustainability, particularly with reference to the fact that their production is based on the use of non-renewable resources.

[0005] Therefore, a common attempt to alleviate this problem is to at least partially replace virgin polyolefin compositions with variable amounts of recycled plastic materials.

[0006] Recycled plastic polyolefins are derived from post-consumer waste (PCW) or post-industrial waste (PIW) streams.

[0007] One of the key problems in polyolefin recycling is the difficulty in quantitatively separating the various types of polymers, so that commercially available recycled products are almost always contaminated with heterogeneous materials from various sources.

[0008] This fact results in the fact that polymer compositions comprising recycled materials are believed to suffer from lower reliability and lower performance relative to compositions made from virgin polymer alone.

[0009] It has now surprisingly been found that when a blend of recycled polymers is added to virgin polypropylene, it is possible to have an improved property profile, in particular with regard to impact and modulus values. Summary of the invention

[0010] Therefore, the object of the present disclosure is a propylene polymer composition having a melt flow rate (ISO 1133 - 1230°C / 2.16kg) value ranging from 3.0 g / 10 min to 70.0 g / 10 min, comprising:

[0011] A) 50 to 80 wt% of a propylene homopolymer or a propylene ethylene copolymer containing up to 22.0 wt% of ethylene, said propylene homopolymer or propylene ethylene copolymer having a melt flow rate (ISO 1133-1230°C / 2.16kg) ranging from 20.0 to 100.0 g / 10min;

[0012] B) 50% to 20% by weight of a blend comprising:

[0013] T1) from 10 to 50 wt% of a propylene ethylene copolymer comprising from 8.0 to 20.0 wt% of ethylene derived units; said copolymer having an MFR (ISO 1133-1190°C, 2.16 kg load) comprised between 0.5 g / 10 min and 5.0 g / 10 min;

[0014] T2) from 50 wt% to 90 wt% recycled polyethylene (r-PE) having a melt flow rate (190°C / 2.16 Kg) from 0.1 g / 10 min to 10.0 g / 10 min and containing a polypropylene content in an amount ranging from 1 wt% to 15 wt% of the total r-PE component, the sum of the amounts of T1 and T2 being 100;

[0015] The sum of the quantities of A) and B) is 100. DETAILED DESCRIPTION

[0016] The object of the present disclosure is a propylene polymer composition having a melt flow rate (ISO 1133230°C / 2.16kg) value ranging from 3.0 g / 10min to 70.0 g / 10min; preferably from 8.0 g / 10min to 45.0 g / 10min; more preferably from 10.0 g / 10min to 35.0 g / 10min, the propylene polymer composition comprising or consisting essentially of:

[0017] A) 50 to 80 wt%; preferably 55 to 75 wt%; more preferably 58 to 72 wt%; even more preferably from 55 to 65 wt% of a propylene homopolymer or a propylene ethylene copolymer containing up to 22.0 wt%; preferably up to 12.0 wt%; more preferably up to 7.0 wt% of ethylene, said propylene homopolymer or propylene ethylene copolymer having a melt flow rate (ISO 1133230°C / 2.16kg) ranging from 20.0 to 100.0 g / 10min; preferably from 60.0 to 90.0 g / 10min; more preferably from 65.0 to 85.0 g / 10min;

[0018] B) 20 to 50 wt. %; preferably from 25 to 45 wt. %; more preferably from 28 to 42 wt. %; even more preferably from 35 to 45 wt. % of a blend comprising:

[0019] T1) from 10 to 50 wt%; preferably from 15 to 40 wt%, more preferably from 20 to 30 wt% of a propylene ethylene copolymer comprising from 8.0 to 20.0 wt%, preferably from 11 to 19 wt%, more preferably from 13 to 18 wt% of ethylene derived units; said copolymer having an MFR (measured at 190°C, 2.16 kg load) comprised between 0.5 and 5.0 g / 10 min; preferably from 0.8 to 3.0 g / 10 min;

[0020] T2) from 50 wt% to 90 wt%; preferably from 60 wt% to 85 wt%, more preferably from 70 wt% to 80 wt% of recycled polyethylene (r-PE) having a melt flow rate (190°C / 2.16 Kg) from 0.1 g / 10 min to 10.0 g / 10 min and containing a polypropylene content in an amount ranging from 1 wt% to 15 wt% of the total r-PE component;

[0021] The sum of the amounts of T1 and T2 is 100;

[0022] The sum of the quantities of A) and B) is 100.

[0023] The term "copolymer" as used herein refers to polymers having two different repeating units in the chain and polymers having more than two different repeating units, such as terpolymers. "Ambient or room temperature" herein means a temperature of 25°C.

[0024] The term "crystalline propylene polymer" is intended in the present application to mean a propylene polymer having an amount of isotactic pentads (mmmm) higher than 70 mol %, the amount of isotactic pentads (mmmm) being determined by 13 C-MNR is measured on the fraction insoluble in xylene at 25°C; by "elastomeric" polymer is meant a polymer whose solubility in xylene at ambient temperature is higher than 50% by weight.

[0025] The term "consisting essentially of" as used herein in conjunction with a polymer or polymer composition means that in addition to the mandatory components, other components may also be present in the polymer or polymer composition, provided that the basic characteristics of the polymer or composition are not substantially affected by their presence. According to the present disclosure, examples of components that do not substantially affect the properties of a polymer or polymer composition when present in conventional amounts are catalyst residues, antistatic agents, melt stabilizers, light stabilizers, antioxidants, antacids.

[0026] The features of the components forming the polypropylene composition are not inseparably connected to each other. This means that a certain degree of preference for a certain feature does not necessarily involve the same degree of preference for the remaining features of the same or different components. On the contrary, it is intended in the present disclosure that the features of any component (A) to (B) and any preferred range of components (A) to (B) can be combined with one or more features of any preferred range of components (A) to (B) and with any possible additional components and their features described in the present disclosure.

[0027] Preferably, component A) is a virgin resin; preferably, component A is a propylene homopolymer.

[0028] The melting temperature of component A) preferably ranges from 135 to 165° C. When component A) is a homopolymer, the melting temperature determined via DSC preferably ranges from 155 to 165° C., while for copolymers it preferably ranges from 135 to 155° C.

[0029] Component A) can be prepared by polymerizing propylene, optionally in a mixture with ethylene, in the presence of a catalyst comprising the reaction product between:

[0030] i) a solid catalyst component comprising Ti, Mg, Cl and at least one internal electron donor compound;

[0031] ii) an alkylaluminum compound, and

[0032] iii) external electron donor compounds having the following general formula:

[0033] (R 7 ) a (R8 ) b Si(OR 9 ) c , wherein a and b are integers from 0 to 2, c is an integer from 1 to 4, and the sum of (a+b+c) is 4; R 7 , R 8 and R 9 is an alkyl, cycloalkyl or aryl radical having 1 to 18 carbon atoms which may optionally contain heteroatoms.

[0034] The internal donor is preferably selected from esters of mono- or dicarboxylic organic acids, such as benzoates, malonates, phthalates and certain succinates. Examples of internal donors are described in US 4522930A, EP 045977A2 and international patent applications WO 00 / 63261 and WO 01 / 57099. Particularly suitable are phthalates and succinates. Alkyl phthalates are preferred, such as diisobutyl phthalate, dioctyl phthalate and diphenyl phthalate and benzyl butyl phthalate.

[0035] The particles of solid component (i) may have a substantially spherical morphology and an average diameter ranging between 5 μm and 150 μm, preferably from 20 μm to 100 μm, and more preferably from 30 μm to 90 μm. As particles having a substantially spherical morphology, those particles are meant in which the ratio between the larger axis and the smaller axis is equal to or lower than 1.5, and preferably lower than 1.3.

[0036] The amount of Mg may preferably range from 8 to 30%, more preferably from 10 to 25 wt%.

[0037] The amount of Ti may range from 0.5 to 7%, more preferably from 0.7 to 5 wt%.

[0038] According to one method, the solid catalyst component (i) can be prepared by reacting a titanium compound of the formula Ti(OR)q-yXy with magnesium chloride derived from an adduct of the formula MgCl2·pROH, wherein q is the valence of titanium and y is a number between 1 and q, preferably TiCl4, wherein p is between 0.1 and 6, preferably a number from 2 to 3.5, and R is a hydrocarbon radical having 1 to 18 carbon atoms. The adduct can be suitably prepared in spherical form by mixing an alcohol and magnesium chloride, operating under stirring conditions at the melting temperature of the adduct (100°C to 130°C). The adduct is then mixed with an inert hydrocarbon immiscible with the adduct, thereby producing an emulsion which is rapidly quenched, causing the adduct to solidify in the form of spherical particles. Examples of spherical adducts prepared according to this procedure are described in USP 4,399,054 and USP 4,469,648. The adduct thus obtained can be reacted directly with the Ti compound, or it can be previously subjected to a thermally controlled dealcoholation (80° C. to 130° C.) to obtain an adduct in which the number of moles of alcohol is generally lower than 3, preferably between 0.1 and 2.5. The reaction with the Ti compound can be carried out by suspending the adduct (dealcoholated or as such) in cold TiCl4; the mixture is heated to 80° C. to 130° C. and maintained at this temperature for 0.5 to 2 hours. The treatment with TiCl4 can be carried out once or more. The electron donor compound can be added during the treatment with TiCl4 in the desired proportions.

[0039] The alkyl-Al compound (ii) is preferably selected from trialkylaluminum compounds, such as, for example, triethylaluminum, triisobutylaluminum, tri-n-butylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum. It is also possible to use alkylaluminum halides, alkylaluminum hydrides or alkylaluminum sesquichlorides, such as AlEt2Cl and Al2Et3Cl3, possibly mixed with the above trialkylaluminums. The Al / Ti ratio is higher than 1 and can preferably range between 50 and 2000.

[0040] Particularly preferred are silicon compounds (iii) wherein a is 1, b is 1, c is 2, R 7 and R 8At least one of them is selected from a branched alkyl, cycloalkyl or aryl group having 3 to 10 carbon atoms, optionally containing heteroatoms, and R9 is a C1-C10 alkyl group, in particular a methyl group. Examples of such preferred silicon compounds are methylcyclohexyldimethoxysilane (C donor), diphenyldimethoxysilane, methyl-tert-butyldimethoxysilane, dicyclopentyldimethoxysilane (D donor), diisopropyldimethoxysilane, (2-ethylpiperidinyl)tert-butyldimethoxysilane, (2-ethylpiperidinyl)tert-hexyldimethoxysilane, (3,3,3-trifluoro-n-propyl) (2-ethylpiperidinyl)dimethoxysilane, methyl (3,3,3-trifluoro-n-propyl) dimethoxysilane. In addition, it is also preferred that a is 0, c is 3, R8 is a branched alkyl or cycloalkyl group optionally containing heteroatoms and R9 is a methyl silicon compound. Examples of such preferred silicon compounds are cyclohexyltrimethoxysilane, tert-butyltrimethoxysilane and tert-hexyltrimethoxysilane.

[0041] The external electron donor compound (iii) is used in such an amount that the molar ratio between the organoaluminium compound and said external electron donor compound (iii) is from 0.1 to 200, preferably from 1 to 100, and more preferably from 3 to 50.

[0042] The polymerization process can be carried out in the gas phase, operating in one or more fluidized bed or mechanically stirred bed reactors, using an inert hydrocarbon solvent as a diluent for slurry polymerization, or using a liquid monomer (e.g. propylene) as a reaction medium for bulk polymerization. If desired, component A can be chemically treated with an organic peroxide to reduce the average molecular weight and increase the melt flow index to the value required for a specific application.

[0043] The component (T1) is endowed with one or more of the following characteristics:

[0044] i) Tensile strength at break (ASTM D638) higher than 4MPa;

[0045] ii) elongation at break (ASTM D638) greater than 1500%; preferably greater than 2000%;

[0046] iii) Flexural modulus (ASTM D 790) ranges from 5 MPa to 30 MPa; preferably from 6 MPa to 17 MPa; even more preferably from 8 MPa to 19 MPa.

[0047] iv) Shore A Hardness (ASTM 2240) ranges from 40 to 90; preferably from 50 to 80; even more preferably from 57 to 75.

[0048] Component T1 may be a propylene ethylene copolymer sold by ExxonMobill under the trade name Vistamaxx (such as Vistamax 6102).

[0049] Component (T2) is a recycled polyethylene PE, which is preferably a crystalline or semi-crystalline high density PE (r-HDPE) selected from commercial PCW (e.g. post-consumer waste from municipalities). Preferably, the r-PE has a density ranging from 0.940 g / cm 3 Up to 0.965g / cm 3 The density (ISO 1183-1), and the melt flow rate (ISO1133-1190°C / 2.16Kg ISO 1133-1) from 0.1g / 10min to 1.0g / 10min.

[0050] Prior to its use, the plastic mixture containing rHDPE undergoes a standard recycling process, including collection, shredding, sorting and washing. Although the sorted rHDPE is composed of a large amount of HDPE, it always contains a small amount of other polymers and / or inorganic components. In particular, the r-PE according to the present disclosure contains a polypropylene content in an amount of from 1 wt % to 15 wt %, preferably from 5 wt % to 10 wt %, of the total r-PE component.

[0051] In a preferred embodiment, the r-PE comprises a crystalline polyethylene fraction, wherein the amount of repeating units derived from propylene in the polyethylene chain is less than 10 wt%, and most preferably they are absent, i.e. most preferably the r-PE is an ethylene homopolymer comprising the above inclusions. Preferably, (r-PE) has a melt flow rate (ISO 1133-1190°C / 2.16Kg ISO 1133-1) of from 0.1 g / 10min to 1.0 g / 10min, and more preferably from 0.1 g / 10min to 0.5 g / 10min.

[0052] Such r-PE is commercially available. An example of a suitable r-PE grade is represented by the ivory or grey version of the grade sold by Lyondellbasell under the trade name Hostalen QCP5603.

[0053] The overall polypropylene composition of the present disclosure preferably shows a tensile modulus value lower than that of component A).In a preferred embodiment the tensile modulus of the overall propylene polymer composition ranges from 750 MPa to 1700 MPa, more preferably from 800 MPa to 1500 MPa.

[0054] The Charpy impact value at 23°C ranges from 20.0Kj / m 2 Up to 3.0Kj / m 2; The Charpy impact value range at 0℃ is from 3.0Kj / m 2 Up to 14.0Kj / m 2 ; The Charpy impact value range at -20℃ is from 2.5.0Kj / m 2 Up to 10.0Kj / m 2 .

[0055] The overall propylene composition of the present disclosure can be obtained by mechanically blending components (A) and (B) according to conventional techniques.

[0056] The final composition comprising components (A) and (B) can be added with conventional additives, fillers and pigments commonly used in olefin polymers, such as nucleating agents, extender oils, mineral fillers and other organic and inorganic pigments. In particular, the addition of inorganic fillers, such as talc, calcium carbonate and mineral fillers, will also improve some mechanical properties, such as flexural modulus and HDT. Talc may also have a nucleating effect.

[0057] The nucleating agent may be added to the composition of the present disclosure, for example, in an amount ranging from 0.05 wt % to 2 wt %, more preferably from 0.1 wt % to 1 wt %, relative to the total weight.

[0058] The propylene polymer composition of the present disclosure can be extruded to form films or sheets for various applications. Particularly preferred is the use of the polypropylene composition for the preparation of sheets for roofing applications.

[0059] The following examples are given to illustrate but not to limit the present disclosure.

[0060] Examples

[0061] Characterization

[0062] Xylene soluble (XS) fraction at 25°C

[0063] 2.5 g of polymer and 250 ml of xylene were introduced into a glass flask equipped with a refrigerator and a magnetic stirrer. The temperature was raised to the boiling point of the solvent within 30 minutes. The resulting clear solution was then kept under reflux and stirred for 30 minutes. The closed flask was then kept in an ice water bath for 30 minutes and then in a constant temperature water bath at 25 ° C for 30 minutes. The resulting solid was filtered on a quick filter paper. 100 ml of the filtrate was poured into a pre-weighed aluminum container, which was heated on a heating plate under a nitrogen stream to remove the solvent by evaporation. The container was then kept in an oven at 80 ° C under vacuum until constant weight was reached. The weight percentage of the polymer soluble in xylene at room temperature was then calculated.

[0064] The content of the xylene soluble fraction is expressed as a percentage of the original 2.5 grams and then expressed as a xylene insoluble percentage (%) by difference (complementary to 100%).

[0065] Melt flow rate (MFR)

[0066] As specified, according to ISO 1133, measured at 190°C or 230°C and a load of 2.16 kg.

[0067] Intrinsic viscosity (IV)

[0068] The sample is dissolved in tetralin at 135°C and then poured into a capillary viscometer. The viscometer tube (Ubbelohde type) is surrounded by a cylindrical glass jacket; this setup allows temperature control with a circulating thermostatic liquid. The downward passage of the meniscus is timed by a photoelectric device.

[0069] The passage of the meniscus in front of the upper lamp starts a counter with a quartz crystal oscillator. When passing the lower lamp, the meniscus stops the counter and the outflow time is recorded: this is converted into an intrinsic viscosity value by Huggins' equation (Huggins, ML, J. Am. Chem. Soc., 1942, 64, 2716), provided that the flow time of the pure solvent under the same experimental conditions (same viscometer and same temperature) is known. [η] is determined using a single polymer solution.

[0070] Polydispersity index : measured by using a parallel plate rheometer of the RMS-800 type sold by RHEOMETRICS (USA) at a temperature of 200°C, operating at an oscillation frequency increasing from 0.1 rad / sec to 100 rad / sec. From the crossover modulus, the PI can be derived by the following equation:

[0071] PI=105 / Gc

[0072] Where Gc is the crossover modulus, which is defined as the value (expressed in Pa) where G'=G", where G' is the storage modulus and G" is the loss modulus.

[0073] Ethylene (C2) content

[0074] Propylene / ethylene copolymer 13 C NMR

[0075] 13 C NMR spectra were obtained on a Bruker Av-600 spectrometer equipped with a cryoprobe, operating at 160.91 MHz in Fourier transform mode at 120 °C.

[0076] At 29.9ppm S ββThe peak of carbon (according to the nomenclature of "Monomer Sequence Distribution in Ethylene-Propylene Rubber Measured by 13C NMR. 3. Use of Reaction Probability Mode" CJ Carman, RA Harrington and CE Wilkes, Macromolecules, 1977, 10, 536) was used as an internal reference. The sample was dissolved in 1,1,2,2-tetrachloroethane-d2 at a concentration of 8 weight / volume % at 120°C. Each spectrum was acquired with 90° pulses with a 15 second delay between pulses, and CPD was used to remove 1H-13C coupling. 512 transient data were stored in 32K data points using a spectral window of 9000 Hz.

[0077] Evaluation of spectral assignments, triplet distribution and composition was performed according to Kakugo ("Carbon-13 NMR determination of monomer sequence distribution in ethylene-propylene copolymers prepared with δ-titanium trichloride-diethylaluminum chloride" M. Kakugo, Y. Naito, K. Mizunuma and T. Miyatake, Macromolecules 1982, 15, 4, 1150-1152) using the following equations:

[0078] PPP=100T ββ / S PPE=100T βδ / S EPE=100T δδ / S

[0079] PEP=100s ββ / S PEE=100S βδ / S EEE=100(0.25S γδ +0.5S δδ ) / S

[0080] S=T ββ +T βδ +T δδ +S ββ +Sβδ +0.25S γδ +0.5S δδ

[0081] The mole percent ethylene content was estimated using the following equation:

[0082] E%mol=100*[PEP+PEE+EEE]. The weight percentage of ethylene content was estimated using the following equation:

[0083]

[0084] Where P%mol is the molar percentage of propylene content, and MW E and MW P are the molecular weights of ethylene and propylene respectively.

[0085] The product of the reaction ratios r1r2 is calculated as follows according to Carman (CJ Carman, RA Harrington and CE Wilkes, Macromolecules, 1977; 10, 536):

[0086]

[0087] The stereoregularity of the propylene sequence is determined by PPP mmT ββ (28.90ppm-29.65ppm) and total T ββ The ratio of (29.80ppm-28.37ppm) was calculated as the mm content.

[0088] density

[0089] Measured according to ISO 1183-1.

[0090] Samples for mechanical testing

[0091] The samples were obtained according to ISO 1873-2:2007.

[0092] Charpy Impact Test: Determined according to ISO 179-1eA and ISO 1873-2.

[0093] Elongation at Yield: Measured according to ISO 527.

[0094] Elongation at break: measured according to ISO 527.

[0095] Breaking stress: measured according to ISO 527.

[0096] Tensile Modulus: Measured according to ISO 527-2.

[0097] Tear resistance: measured on 1 mm thick extruded sheets according to method ASTM D 1004. Crosshead speed: 51 mm / min; V-die cut specimens.

[0098] Shore D: Measured according to method ISO 868 (15 seconds) on injection molded, compression molded plaques and extruded sheets.

[0099] Shore A: Measured according to ASTM D2240 on injection molded specimens.

[0100] Density: Measured according to ASTM D792.

[0101] Melting point and crystallization point

[0102] Melting points were measured using a DSC instrument according to ISO 11357-3, both under cooling and heating at a scan rate of 20°C / min under an inert N2 flow on samples weighing between 5 mg and 7 mg. Indium was used for instrument calibration.

[0103] Determination of PP content in r-PE

[0104] 13 C NMR spectra were obtained on a Bruker Av-600 spectrometer equipped with a cryoprobe, operating at 160.91 MHz in Fourier transform mode at 120 °C.

[0105] The peak of CH2 ethylene at 29.9 ppm was used as an internal reference. The samples were dissolved in 1,1,2,2-tetrachloroethane-d2 at 8 wt / vol% at 120 °C. Each spectrum was acquired with 90° pulses, a 15 s delay between pulses and CPD to remove 1 H- 13 C coupling. 512 transients were stored in 32K data points using a spectral window of 9000 Hz.

[0106] The molar composition was obtained using the peak areas as follows (Table 1):

[0107] P=100A3 / S

[0108] E=1000.5A2 / S

[0109] Where S = 0.5A2 + A3

[0110] The molar contents were converted to weights using the monomer molecular weights.

[0111] Table 1: Distribution of PP / PE blends

[0112] serial number Chemical shift (ppm) carbon sequence 1 48.8-45.4 <![CDATA[CH2]]> P 2 29.9 <![CDATA[CH2]]> E 3 29.0-28.0 CH P 4 21.8-19.8 CH3 P

[0113] Examples

[0114] Component A)

[0115] Component A) is a commercial homopolymer sold by Lyondellbasell as HA840R. The homopolymer has been visbroken with peroxide to achieve an MFR of 70 g / 10 min.

[0116] Component T1)

[0117] Component T1 is a commercial propylene-ethylene elastomer sold by ExxonMobill under the trade name Vistamaxx 6102. The properties of the copolymer are reported in Table 2.

[0118] Table 2

[0119]

[0120]

[0121] Component T2

[0122] Component T2 has a viscosity of 0.95 g / cm 3 Commercial grade QCP5603 ivory (r-PE commercialized by Lyondellbasell, which contains 10% by weight of PP content) having a density of 0.05 g / 10 min and a melt index "E" of 0.3 g / 10 min.

[0123] Example 1

[0124] The polymer granules of component A) were introduced into an extruder (Berstorff extruder) to which 1000 ppm of MS168 had been added as additive, where they were mixed with the different amounts of components T1 and T2 reported in Table 2. The polymer granules were extruded in a twin-screw extruder under a nitrogen atmosphere at a rotation speed of 250 rpm and a melt temperature of 200° C. to 250° C. The characterization of the resulting compositions is reported in Table 3.

[0125] Table 3

[0126] Example 1 Component A 60 Component B 40 Component T1 (in B) 25 Component T2 (in B) 75 MFR, g / 10min 8.5 Tm℃ 162.9 Tc℃ 1202.6 <![CDATA[Tensile modulus; (N / mm 2 )]]> 1020 <![CDATA[Charpy impact at 23 °C, Kj / m 2 > 10.2 <![CDATA[Charpy impact at 0 °C, Kj / m 2 > 6.7 <![CDATA[Charpy impact - 20 °C Kj / m 2 > 4.6 D / TTT℃ ≤-50

[0127] The above data show that polymer compositions according to the present disclosure have an improved balance of softness and mechanical properties.

Claims

1. A propylene polymer composition having a melt flow rate (ISO 1133230°C / 2.16kg) value ranging from 3.0 g / 10 min to 70.0 g / 10 min, comprising: A) 50 to 80 wt% of a propylene homopolymer or a propylene ethylene copolymer containing up to 22 wt% of ethylene, said propylene homopolymer or propylene ethylene copolymer having a melt flow rate (ISO 1133-1230°C / 2.16kg) ranging from 20.0 to 100.0 g / 10min; B) 50% to 20% by weight of a blend comprising: T1) from 10 to 50 wt% of a propylene ethylene copolymer, said propylene ethylene copolymer comprising from 8.0 to 20.0 wt% of ethylene derived units; said copolymer having an MFR (measured at 190°C, 2.16 kg load) comprised between 0.5 and 5.0 g / 10 min; T2) from 50 wt% to 90 wt% recycled polyethylene (r-PE) having a melt flow rate (ISO 1133-1190°C / 2.16Kg) from 0.1 g / 10 min to 10.0 g / 10 min and containing a polypropylene content in an amount ranging from 1 wt% to 15 wt% of the total r-PE component, the sum of the amounts of T1 and T2 being 100; The sum of the quantities of A) and B) is 100.

2. The propylene polymer composition according to claim 1, wherein the component (A) ranges from 55 wt% to 75 wt%; and the component (B) ranges from 25 wt% to 45 wt%.

3. The propylene polymer composition according to claim 1 or 2, wherein T1 ranges from 15 to 40 wt% and T2 ranges from 60 to 85 wt%.

4. The propylene polymer composition according to any of the preceding claims, wherein T1 has an MFR (ISO 1133 - 1190°C, 2.16 kg load) ranging from 0.8 to 3.0 g / 10 min.

5. The propylene polymer composition according to any of the preceding claims having a melt flow rate (ISO 1133 230°C / 2.16kg) ranging from 8.0 to 45.0 g / 10min.

6. The propylene polymer composition according to any of the preceding claims, wherein component (A) has a melt flow rate ranging from 60.0 g / 10 min to 90.0 g / 10 min.

7. The propylene polymer composition according to any of the preceding claims, wherein component (A) is a propylene homopolymer.

8. The propylene polymer composition according to any of the preceding claims, wherein component (A) ranges from 58 to 72 wt% and component B ranges from 35 to 45 wt%.

9. The propylene polymer composition according to any of the preceding claims, wherein (T1) ranges from 20 to 30 wt.-%, and T2 ranges from 70 to 80 wt.-%.

10. The polypropylene composition according to anyone of the preceding claims, wherein component (T2) has a PP content in an amount ranging from 5 to 10 wt.-%, based on the total amount of component (T2).

11. The polypropylene composition according to any one of the preceding claims, wherein component (T2) has a molecular weight ranging from 0.940 g / cm 3 Up to 0.965g / cm 3 The density (ISO 1183-1) and the melt flow rate (190°C / 2.16Kg ISO 1133-1) range from 0.1 g / 10 min to 1.0 g / 10 min.

12. Propylene polymer composition according to any of the preceding claims, wherein component T1 comprises from 11.0 to 19.0 wt% of ethylene derived units.

13. Propylene polymer composition according to any of the preceding claims, wherein component T1 has a Shore A hardness (ASTM 2240) ranging from 50 to 80.

14. Propylene polymer composition according to any of the preceding claims, wherein component T1 comprises from 13.0 to 18.0 wt% of ethylene derived units.

15. An extruded article obtained from the propylene polymer composition according to any of the preceding claims.

Citation Information

Patent Citations

  • Components and catalysts for the polymerization of olefins

    EP0045977A2

  • Elastoplastic polyolefin compositions

    EP0472946A2

  • Components and catalysts for the polymerization of olefins

    US4522930A

  • Components and catalysts for the polymerization of olefins

    WO2000063261A1

  • Components and catalysts for the polymerization of olefins

    WO2001057099A1